New englishes, new methods - Wilson, Guyanne; Westphal, Michael (Varieties of English around the world, 2023)
There is an ever-growing body of work on New Englishes, and the time has come to take stock of how research on varieties of English is carried out. The contributions in this volume critically explore the gamut of familiar and unfamiliar methods applied in data collection and analysis in order to improve upon old methods and develop new methods for the study of English around the world. The authors present novel approaches to the use of the International Corpus of English, critical insights into phonological analyses of New Englishes, applications of linguistic dialectology in territories in which New Englishes are used, improvements on attitudinal research, and an array of mixed-methods approaches. The contributions in this volume also include a range of Englishes, considered not only in situ but also in online and diaspora settings, and thus question received understandings of what counts as New Englishes.
Keywords: Konferenzschrift; Forschungsmethode; Sprachvariante; Englisch; Globalisierung; Sprachkontakt